Investigation on the interfacial mechanical properties of hybrid graphene-carbon nanotube/polymer nanocomposites. (May 2017) - Liu, Feng; Hu, Ning; Ning, Huiming; Atobe, Satoshi; Yan, Cheng; Liu, Yaolu; Wu, Liangke; Liu, Xuyang; Fu, Shaoyun; Xu, Chaohe; Li, Yuanqing; Zhang, Jianyu; et al.
Abstract: A remarkable synergetic effect between the graphene (GR) and carbon nanotube (CNT) in improving the interfacial mechanical properties of polyethylene polymer composites was investigated using molecular dynamics simulations. The reinforcement effects of two types of hybrid GR-CNT were evaluated. For the π − π stack hybrid GR-CNT, the alignment of CNT has a slight effect on the interfacial mechanical properties. For the covalent bond hybrid GR-CNT, the reinforcement effect increases with the CNT's length and radius, and multi-walled carbon nanotube is more efficient than single-walled carbon nanotube. With the same parameters of CNT, the interfacial mechanical properties of π − π stack hybrid GR-CNT is superior to the covalent bond hybrid GR-CNT. Compared with GR, the hybrid GR-CNT can effectively enhance the interfacial mechanical properties due to the synergetic effect between the GR and the CNT. Graphical abstract: